Application of hospital-community-family health education to family caregivers of nasal fed patients under the background of a regional medical association - Shi, Zhijing; Zhao, Yangyi; Jin, Luchen; Chen, Xiaoe; Huang, Jin (American journal of translational research, 2022)
Patients with nasogastric tube (NTG) nutrition after discharge still need to be transferred to community hospitals for continued care. Effective health education is conducive to raising the level of knowledge of caregivers to promote the rehabilitation of patients. Clinical data of 65 caregivers of stroke patients in Putuo Hospital affiliated to Shanghai University of Traditional Chinese Medicine from June 2020 to December 2020 were retrospectively analyzed. These caregivers were divided into an observation group (33 cases, hospital-community-family education model) and a control group (32 cases, routine nursing health education). We used questionnaires to assess the knowledge, attitudes, and practice levels of caregivers before and after education, and recorded the occurrence of complications in patients within 12 weeks. The scores of the knowledge questionnaire and practice questionnaire of caregivers in the observation group were higher than those in the control group at 2, 4 and 12 weeks after intervention (P<0.05). The scores of caregivers' attitudes questionnaire were higher in the observation group than in the control group at 4 and 12 weeks after intervention (P<0.05). But 2 weeks after intervention, there was no significant difference between the two groups (P>0.05). Within 12 weeks after intervention, the probability of complications in observation group was lower than that in the control group (P<0.05). Logistic regression analysis showed that the hospital-community-family health education helped the outcome. For the main caregivers of NTG nutrition patients, the implementation of a hospital-community-family health education model based on regional medical consortium can improve the level of knowledge, attitude and practice of caregivers' NTG nutrition skills and reduce complications in patients.